A hot and luminous source at the site of the fast transient AT2018cow at 2–3 yr after its explosion. Issue 1 (8th March 2022) - Sun, Ning-Chen; Maund, Justyn R; Crowther, Paul A; Liu, Liang-Duan
ABSTRACT: We report the discovery of a luminous late-time source at the position of the fast blue optical transient AT2018cow on images taken by the Hubble Space Telescope at 714 d and 1136 d after its explosion. This source is detected at both UV and optical wavelengths and has prominent Hα emission. It has a very stable brightness between the two epochs and a very blue spectral energy distribution consistent with f λ λ ^-4.1 ± 0.1, i.e. the Rayleigh–Jeans tail of a hot blackbody with a very high temperature of log( T /K) > 4.7 and luminosity of log( L / L ⊙ ) > 7.0. This late-time source is unlikely to be an unrelated object in chance alignment, or due to a light echo of AT2018cow. Other possible scenarios also have some difficulties in explaining this late-time source, including companion star(s), star cluster, the survived progenitor star, interaction with circumstellar medium, magnetar, or delayed accretion in a tidal disruption event. Long-term and multi-wavelength monitoring will help to resolve its nature and finally reveal the origin of the 'Cow'.